Analysis Of The Influencer Content On Advertising Behavior And Consumer Purchase Intention (Case Study On Beauty Influencer Tasya Farasya): English - Mozafisa Alfisahar; Asma’i Ishak (International Journal of Economics, Business and Innovation Research, 2024)
This research was conducted to examine the influence of content delivered by influencer Tasya Farasya on advertising behavior and purchasing interest felt by consumers. This research used a quantitative approach with data collection methods using questionnaires and obtained a total of 196 respondents. Data analysis techniques were carried out descriptively and statistically using SEM AMOS. The findings of this research are: 1) Infotainment influences ads value positively and significantly, 2) Credibility influences ads value positively and significantly, 3) Irritation influences ads value negatively and significantly, 4) Ads value influences behavior towards advertising positively and significant, 5) Ads Value influences purchasing interest positively and significantly, 6) Behavior towards advertising influences purchasing interest positively and significantly.